Crosstalk between bone and muscle in chronic kidney disease - Wong, Limy; McMahon, Lawrence P. (Frontiers in Endocrinology, 2023)
With increasing life expectancy, the related disorders of bone loss, metabolic dysregulation and sarcopenia have become major health threats to the elderly. Each of these conditions is prevalent in patients with chronic kidney disease (CKD), particularly in more advanced stages. Our current understanding of the bone-muscle interaction is beyond mechanical coupling, where bone and muscle have been identified as interrelated secretory organs, and regulation of both bone and muscle metabolism occurs through osteokines and myokines via autocrine, paracrine and endocrine systems. This review appraises the current knowledge regarding biochemical crosstalk between bone and muscle, and considers recent progress related to the role of osteokines and myokines in CKD, including modulatory effects of physical exercise and potential therapeutic targets to improve musculoskeletal health in CKD patients.